Deterring Plagiarism in Algerian Universities: A Focus on the Legal Measures and their Efficacy - Ahlem Hedjaz; Abdellah Baraka (مجلة الاجتهاد للدراسات القانونية والاقتصادية)
There is no doubt that plagiarism has become a growing ethical dilemma which hits the scientific research world and publishing. Recent studies have shown a considerable concern about the issue to gain a deep insight into the phenomenon, understand its roots and find solutions to prevent or at least minimize its spread. The Algerian legislator has realised that plagiarism is a plague that tarnishes the reputation of Algerian universities worldwide therefore finding the ways to deter it becomes a necessity. In a move to fight against this phenomenon, legal measures have been taken into action. Those measures presented in the ministerial resolution n°933 and 1082 equate plagiarism to criminal and immoral behaviour and set preventive and punitive regulations to ensure integrity in academia. The research in hand aims at investigating the issue of plagiarism from a legal perspective. It sheds light on analysing the legal measures taken by the Algerian authorities to deter plagiarism and assessing their efficacy in reality. The study shows the multidimensionality of the phenomenon therefore it recommends a myriad of approaches to deter it.